Age Specific Prevalence of Thyroid Dysfunction in Women from Northern Part of Bangladesh: A Cross-Sectional Study (Jagannath University Journal of Life and Earth Sciences, 2025)
Thyroid dysfunction, especially among women, poses a significant global health issue. The people living in the northern part of Bangladesh are particularly vulnerable to thyroid dysfunction, yet it has not received much attention. The objective of this research was to investigate the occurrence of thyroidism across different life stages, which include childhood, puberty, youth, mid-age, and post-menopause. Using the 125I- RIA method, the study analyzed the serum TSH, fT3, and fT4 levels of 295 subjects at the Institute of Nuclear Medicine and Allied Sciences (INMAS), Rajshahi. The results showed that the overall percentage of affected women was 12.9%. The prevalence of dysfunction was minimal in childhood (10.0%) and puberty (4.3%), peaked in mid-life (29.8%), and then declined in post-menopause (10.2%). The study identified hypothyroidism as the most common form of dysfunction among the positive cases. Notably, mid-age individuals experienced the highest incidence of total hypothyroidism, whereas total hyperthyroidism was most prevalent in the youth stage. This research offers a comprehensive insight into the thyroid status of women in North-Bengal, which can be used to address relevant health concerns.Jagannath University Journal of Life and Earth Sciences, 10(1) 17-23